Chongqing 2035 : Spatial Transformation Strategy - World Bank (World Bank, Washington, DC, 2019)
Chongqing Municipality, located in the southwest of inland China and upstream of the Yangtze River, is one of the largest cities in the world, with an area of 82,400 km2 and population of 33.92 million (Chongqing Municipal Bureau of Statistics and NBS Survey Office in Chongqing 2016). To put it in perspective, the municipality’s area is as large as that of Austria and its population is close to that of Canada. This report is based on two analytical streams: 1) an assessment of Chongqing’s issues and challenges at municipality and central city scales based on the trends of the past 20 years, benchmarked with other provincial-level municipalities in China and with global cities to derive policy lessons for Chongqing; and 2) a scenario analysis comparing a Trend scenario and a Compact Growth scenario for central Chongqing.